Efficient Echocardiographic Image Segmentation. (10th September 2022) - Khan, Muhammad Salim; Saqib, Laiba; Shah, Zahir; Ali, Haider; Alshehri, Ahmad
Abstract : In this paper, we propose an improved region-based active contour method based on the development of a novel signed pressure force (SPF) function. To obtain the required boundary, the method is applied to the echocardiographic images. Ultrasound image segmentation is particularly challenging due to speckle noise, low contrast, and intensity inhomogeneity. Because of these factors, segmenting echocardiographic images is a difficult task. All of these issues are addressed by the proposed model, which detects the true boundary without any noise. The proposed model is more robust, effective, and accurate when applied to images with weak edges and inhomogeneous intensity.